2020
DOI: 10.1002/dmrr.3373
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating follistatin‐like‐1 and metabolic syndrome in middle‐aged and old population: A cross‐sectional study

Abstract: Aim Follistatin‐like‐1 (FSTL‐1) is considered to be a novel cytokine, and it is associated with metabolic diseases. However, it is necessary to investigate further the association of FSTL‐1 with metabolic syndrome (MetS) and insulin resistance (IR). We performed a cross‐sectional study to investigate the associated of circulating FSTL‐1 with the MetS. Materials and methods A cross‐sectional study was performed in 487 Chinese people, including 231 control subjects and 256 patients with MetS. Bioinformatics anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Berger et al demonstrated that FN1 is one of the adipocyte-specific dysregulated genes in obese adipose tissues [ 38 ]. Similar findings were implied by Yang et al when they found that FN1 is strongly associated with metabolic syndrome (MetS) and insulin resistance (IR) [ 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…Berger et al demonstrated that FN1 is one of the adipocyte-specific dysregulated genes in obese adipose tissues [ 38 ]. Similar findings were implied by Yang et al when they found that FN1 is strongly associated with metabolic syndrome (MetS) and insulin resistance (IR) [ 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…To investigate the relationship between CTRP7 and IR, study populations were divided into IR and non-IR according to HOMA-IR > 3 or ≤ 3 ( 24 ). The results showed that IR population had higher serum CTRP7 levels [195.4 (163.3-244.7) vs. 130.6 (103.1-173.6) μg/L; p < 0.01, Figure 1C ] and lower APN levels [5.19 (2.90-8.76) vs. 8.07 (4.67-1.39) mg/L, p < 0.01) compared with non-IR population ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…An interaction score of 0.4 was considered a cut-off criterion, and the PPI was visualized. The cluster Profiler package was used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses ( 24 ). REACTOME enrichment analysis was completed by a STRING database ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Martin Horak et al showed in their study that overweight and moderate obesity are associated with increased levels of FSTL1 primarily due to its pro-inflammatory action during chronic mildly inflammatory condition [102]. On the other hand, pathological and severe obesity decreased FSTL1 levels due to a continuous increase in the number of matured adipocytes and other associated factors [102][103][104]. In addition, the secretion of FSTL1 may be regulated by hyperinsulinemia and free fatty acids [105][106][107].…”
Section: Pathologies Of Osteo-and Myohistogenesismentioning
confidence: 99%